Fabrication and performance of a carbon dioxide-tolerant proton-conducting solid oxide fuel cells with a dual-layer electrolyte - Guo, Y.; Ran, R.; Shao, Zongping (Elsevier Ltd, 2010)
A proton-conducting solid oxide fuel cells with a dual-layer electrolyte, constructed of a highly protonic conductive BaCe0.8Y 0.2O3-d (BCY) electrolyte and chemically stable BaZr0.4Ce0.4Y0.2O3-d (BZCY4) electrolyte, was easily fabricated by dry pressing the electrolyte powders onto an NiO + BZCY4 anode substrate, followed by co-sintering at a high temperature. The performance of the as-fabricated cell with the BCY and BZCY4 dual-layer electrolyte was studied. Peak power densities of 249 and 101 mW cm-2 were achieved at 700 and 500 °C, respectively. Zinc was applied as a sintering promoter to increase the relative density of the BZCY4 electrolyte. Cross-sectional micrographs of the as-fabricated, dual-layer electrolyte cells were obtained by scanning electron microscopy. The results showed that the sintering ability of BZCY4 was improved by using zinc as sintering aid. A cell with BCY and zinc-modified BZCY4 dual-layer electrolyte delivered peak power densities of 276 and 247 mW cm-2 and OCVs of 1.03 and 1.02 V at 700 °C under humidified hydrogen and 15% CO2-containing hydrogen atmospheres, respectively. The operation stability of the dual-layer electrolyte cell under a 15% CO2-containing hydrogen atmosphere was also investigated. © 2010 Professor T. Nejat Veziroglu. Published by Elsevier Ltd. All rights reserved.